FRI0143 Prevalence and determinants of peripheral endothelial dysfunction in a cohort of rheumatoid arthritis patients: preliminary results from a multicenter cross-sectional study. (15th June 2017) - Erre, GL; Piga, M; Fedele, AL; Cadoni, ML; Sante, G Di; Cangemi, I; Piras, A; Dessì, M; Mura, S; Tolusso, B; Longu, MG; Saba, PS; et al.
Abstract : Background: RA patients suffer of a life expectancy significantly reduced with respect to the general population mainly due to cardiovascular (CV) disease. Endothelial dysfunction (ED), the early step in atherosclerotic process, is more evident in RA than in the general population. Peripheral arterial tonometry (PAT), a simple, rapid, and objective tool for evaluation of ED, measures small digital artery reactive hyperaemia after an ischemic stimulus in forearm. PAT shows high grade of correlation with coronary ED and predicts future CV events in the general population. Objectives: To define prevalence and determinants of peripheral ED in RA. Methods: Data from 633 RA patients free of previous CV events prospectivelly enrolled in the EDRA study* (ClinicalTrials.gov: NCT02341066 ) were analysed. Reactive hyperemia index (LnRHI) was evaluated by PAT using the EndoPAT2000 device: ED was defined by LnRHI <0.51. Linear and logistic regression analysis were performed to define independent predictors of ED in RA patients. A p-value <0.05 was considered statistically significant. Results: Peripheral ED was documented in 212 out of 633 RA patients (33.3%). A linear regression for multiple variables (stepwise method) performed including into the models variables showing significant association with LnRHI at the univariate regression analysis (systolic blood pressure, HDL cholesterol levels, triglycerides levels, smoking habit and ACPA positivity; Age and gender were forced) showed that only higher levels of triglycerides [B coefficient (95%IC) = -0, 001 (-0, 001–0, 00); p <0.05] negativity for ACPA [B coefficient (95%IC) = -0, 070 (-0, 135–0, 005); p <0.05] and smoking habit [B coefficient (95%IC) =0, 01 (0, 043–0, 156); p <0.05] were independently related to lower values of LnRHI. No significant correlation between peripheral ED and RA activity (DAS-28, CDAI, SDAI, HAQ), burden of systemic inflammation (CRP, ESR) and type of immunosuppressive treatment (steroids, NSAIDs, DMARDs and bDMARDs) was found. At logistic regression analysis ACPA negativity [OR ((95%IC) = 1.57 (1.04–2.21); p <0.05] and smoking habit [OR ((95%IC) = 1.64 (1.06–2.53); p <0.05] indipendently conferred a major risk of peripheral ED. Conclusions: This study demonstrates for the first time a very high prevalence of peripheral ED in patient with RA free of previous CV events. Triglycerides levels and smoking habit, among traditional cardiovascular risk factor, showed a significant correlation with lower peripheral ED. Surprisingly ACPA negativity confers an increased risk for ED in RA population. Moreover, other than expected, systemic inflammation does not appear to influence peripheral ED in RA population. In conclusion our data further support the notion that atherogenesis in RA is only partially driven by traditional CV factors. The negative association between ACPA and ED warrants further investigation. Acknowledgements: *The EDRA study is a project funded by Italian Ministry of Health and by Regione Sardegna (RAS) (GR-2011–02352816; Ricerca Finalizzata 2011). Disclosure of Interest: None declared